Methodology For Developing Visual AbilitiesAnd Creativity In Preschool Children - Sulaymonova Shaxnoza Qandiyor qizi (Euro Asian Journal Publishing, 2025)
The content of the article talks about the ways of forming and developing the manifestation of identity among the students of the preschool educational organization, and this problem is educational. the theoretical basis for determining the content of the pedagogical method of enabling children to promote their identity during game training It was analyzed as a result of studies and practical experiments.
Keywords: educational game; self-awareness; self-existence